2020
DOI: 10.1055/a-1162-9988
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Products in Postsurgical Wound Healing – Incision, Excision and Dead Space Wound Models

Abstract: The purpose of this review is to summarize current knowledge acquired on preclinical (incision, excision, and dead space wound models) and clinical studies regarding topically used herbal products with wound healing activity. The antimicrobial, anti-inflammatory, and antioxidant mechanisms of their action as well as the adverse effects of herbal therapy will be described. Numerous preclinical and few clinical trials have confirmed the activity of herbal products in the stimulation of wound healing. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Most of the included studies reported on and discussed the potential ability of M. oleifera in accumulating collagen, the most important protein for wound recovery [ 9 , 34 , 46 ]. Collagen formation is an important step in wound healing, as synthesized collagen will enhance epithelialization, a key factor in excision wound recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included studies reported on and discussed the potential ability of M. oleifera in accumulating collagen, the most important protein for wound recovery [ 9 , 34 , 46 ]. Collagen formation is an important step in wound healing, as synthesized collagen will enhance epithelialization, a key factor in excision wound recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the wound burden towards healthcare and the economy, new therapeutic approaches and technologies are continually being developed [ 8 ]. At the same time, studies to evaluate the efficacy of documented traditional approaches for wound healing, such as herbs [ 9 , 10 , 11 , 12 , 13 ], or other alternative methods, such as leech therapy [ 14 , 15 ], are also conducted. An ideal wound dressing should be non-toxic and cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…It is then on a suitable model of the wound healing process that ADHE properties have been tested in this study. Evaluation of the wounds surfaces and the rate of contraction of these wounds, a parameter that characterizes the closure of the wound (Darré et al, 2014), indicated that ADHE incorporated in Carbopol gel and administrated topically accelerated the wound Considering that the cicatrization of an injured skin is a complex process involving multiple mechanisms such as collagen production, inflammatory cells signaling and free radicals management (Herman and Herman, 2020), we investigated in vivo the hydroxyproline production and in vitro the anti-inflammatory and antioxidant activities of ADHE. The measurement of hydroxyproline is frequently used as a reliable index to quantify collagen in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Wounds have happened due to the loss of histological composition of the skin tissue due to internal or external factors or sequential loss of function in any layer of the skin, which leads to tissue disturbance (Herman and Bordoni 2020). The existence of wounds permits the entrance of different microbial agents as bacteria and viruses or any foreign elements, into the body.…”
Section: Introductionmentioning
confidence: 99%